Employees’ satisfaction with HR hiring and selection policy of DHL worldwide express (BD) Pvt. Ltd. - Rozario, Paola Agnes (BRAC University, 2017)
This internship report is submitted in a partial fulfilment of the requirements for the degree of Masters of Business Administration, 2017.